Optical spectra of small CdS nanocrystals - Boichuk, V.I.; Leshko, R.Ya.; Holskyi, V.B.; Karpyn, D.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Determined in this work is the energy of surface states related with polarization charges at the interfaces. This energy was compared with that of electron internal states. Dipole momentum matrix elements of the interlevel transition were also determined. The value of interlevel absorption coefficient versus the electromagnetic wave frequency was calculated.